Yavia crypthocarpa: Conservation action of a new and interesting cactus - Kiesling, Roberto (2001)
A new genus and species is described: Yavia crytocarpa R. Kiesling & Piltz, from the border of Argentina with Bolivia, in the province of Jujuy, Department Yavi, at 3700 m a. s. l. The new monotypic genus is characterized by the hidden fruits which are sunken into the single stem for several months drops out only in the late spring, when the new buds develop, just at the beginning of the rainy season. The fruits have the uncommon character to loose the dry perianth, as happens frequently at the subfamily Opuntioidae, but very rarely at Cactoideae. The putative relationships with Blossfeldia, Cintia, Neowerdermannia and Weingartia are discussed.A new genus and species is described: Yavia crytocarpa R. Kiesling & Piltz, from the border of Argentina with Bolivia, in the province of Jujuy, Department Yavi, at 3700 m a. s. l. The new monotypic genus is characterized by the hidden fruits which are sunken into the single stem for several months drops out only in the late spring, when the new buds develop, just at the beginning of the rainy season. The fruits have the uncommon character to loose the dry perianth, as happens frequently at the subfamily Opuntioidae, but very rarely at Cactoideae. The putative relationships with Blossfeldia, Cintia, Neowerdermannia and Weingartia are discussed.Blossfeldia, Cintia, Neowerdermannia and Weingartia are discussed. Sumario: Se describe un nuevo genero y especie: Yavia cryptocarpa R. Kiesling & Piltz, del limite de Argentina con Bolivia, en la provincia de Jujuy, a 3700 m s.m. El nuevo genero monotipico se caracteriza por los frutos que se mantienen protegidos en la depresion central de la planta por varios meses, siendo expulsados recien al final de la primavera, al desarrollarse los botones florales, al comienzo de la epoca de lluvias. Ademas, los frutos poseen el caracter poco frecuente de tener el perianto deciduo, como occure frecuetemente en la subfamilia Opuntioideae, pero mas raramente en Cactoideae. Se especula sobre las posibles relaciones con Blossfeldia, Cintia, Neowerdermannia y Weingartia.Se describe un nuevo genero y especie: Yavia cryptocarpa R. Kiesling & Piltz, del limite de Argentina con Bolivia, en la provincia de Jujuy, a 3700 m s.m. El nuevo genero monotipico se caracteriza por los frutos que se mantienen protegidos en la depresion central de la planta por varios meses, siendo expulsados recien al final de la primavera, al desarrollarse los botones florales, al comienzo de la epoca de lluvias. Ademas, los frutos poseen el caracter poco frecuente de tener el perianto deciduo, como occure frecuetemente en la subfamilia Opuntioideae, pero mas raramente en Cactoideae. Se especula sobre las posibles relaciones con Blossfeldia, Cintia, Neowerdermannia y Weingartia.Blossfeldia, Cintia, Neowerdermannia y Weingartia.